Web-GIS and Artificial Intelligence A Panacean for Agriculture Advancement in Developing Countries - A Review (American Journal of Geospatial Technology, 2024)
Agricultural contributions to the economies of developing countries, including Nigeria, have been declining. This paper proposes leveraging Web-GIS and artificial intelligence (AI) to rejuvenate agriculture in these regions. It aims to dissect the components of Web GIS, examine spatial data capture methods, delve into AI for image processing, and develop revenue-generating strategies to boost Nigeria’s agricultural sector. Despite substantial capital investment, agricultural outputs remain below expectations, primarily due to informational gaps regarding land use, planting techniques, and storage. The bureaucratic management of public agricultural sectors further delays disseminating research findings to farmers. Adopting Web-GIS and AI offers a modern solution to these challenges, facilitating real-time analysis and communication of vital information related to soil conditions, farmer challenges, and broader socio-economic and environmental concerns. This approach promises to elevate agricultural practices by integrating technologies like the Internet of Things, GIS, and extensive data-sharing capabilities across the web. The paper emphasizes the potential of ubiquitous smartphone use and widespread internet connectivity to transform agricultural information dissemination. It advocates for leveraging the digital infrastructure of smart cities to enhance access to agricultural data, ultimately improving farming practices across Nigeria. The fusion of Web-GIS and AI with existing telecommunications networks presents a viable path forward, enabling farmers to make informed decisions, improve productivity, and contribute more significantly to the national economy.